How to measure, report and verify soil carbon change to realise the potential of soil carbon sequestration for atmospheric greenhouse gas removal - Smith, Pete; Soussana, Jean‐Francois; Angers, Denis; Schipper, Louis; Chenu, Claire; Rasse, Daniel P.; Batjes, Niels H.; Egmond, Fenny van; McNeill, Stephen; Kuhnert, Matthias; Arias Navarro, Cristina; Olesen, Jørgen E.; et al. (Wiley, 2020)
There is growing international interest in better managing soils to increase soil organic carbon content to contribute to climate change mitigation, to enhance resilience to climate change and to underpin food security, through initiatives such as international “4p1000″ initiative and the FAO's Global assessment of soil organic carbon sequestration potential (GSOCseq) programme. Since soil organic carbon content of soils cannot be easily measured, a key barrier to implementing programmes to increase soil organic carbon at large scale, is the need for credible and reliable measurement/monitoring, reporting and verification (MRV) platforms, both for national reporting and for emissions trading. Without such platforms, investments could be considered risky.